Disaster, Displacement and International Law: Legal Protections in the Context of a Changing Climate - Cullen, Miriam (2020)
As the number of people displaced by disaster reaches record highs, this article describes how international law is relevant to disaster displacement, how refugee law is probably not the answer, and synthesises recent developments into contemporary application. New interpretations of international human rights law have advanced legal protections such that planning and preparedness to address future disasters now form an express component of states’ international legal obligations. At the same time, climate change is increasing the frequency and intensity of extreme weather events, exacerbating factors that cause disaster and displacement and rendering the effective implementation of international law more difficult. The further ‘othering’ of migrants during the Covid-19 pandemic could stymie the realisation of protections as national governments close borders, anti-immigration sentiment is stoked, and economies decline.